Floating thrombus in the ascending aorta revealed by peripheral arterial embolism. (20th February 2020) - Gueldich, Majdi; Piscitelli, Mariantonietta; Derbel, Haytham; Boughanmi, Khaoula; Bergoend, Eric; Chanai, Nora; Folliguet, Thierry; Fiore, Antonio
Abstract: A floating thrombus in the ascending aorta is rarely found in clinical practice and is an uncommon cause of peripheral arterial embolization. When there is minimal atherosclerosis or a normal aorta, the management of such a lesion is poorly defined. Currently, there is no clear consensus concerning optimal treatment. Herein, we report 2 cases of ascending aortic thrombus that are complicated by a peripheral embolic event. Due to the risk of recurrent systemic embolism, particularly with strokes, surgical thrombectomy with ascending aortic wall replacements was performed. We believe that floating ascending aorta thrombus represents a serious source of systemic embolism and stroke. Surgical removal is easy to perform with good clinical outcomes. Conservative treatments such as anticoagulation or thromboaspiration may be considered in high-risk or inoperable patients.